Dominant-currency pricing and the global output spillovers from US dollar appreciation - Georgios Georgiadis; Ben Schumann (European Central Bank (ECB), 2019)
Different export-pricing currency paradigms have different implications for a host of issues that are critical for policymakers such as business cycle co-movement, optimal monetary policy, optimum currency areas and international monetary policy co-ordination. Unfortunately, the literature has not reached a consensus on which pricing paradigm best describes the data. Against this background, we test for the empirical relevance of dominant-currency pricing (DCP). Specifically, we first set up a structural three-country New Keynesian dynamic stochastic general equilibrium model which nests DCP, producer-currency pricing (PCP) and local-currency pricing (LCP). In the model, under DCP the output spillovers from shocks that appreciate the US dollar multilaterally decline with an economy's export-import US dollar pricing share differential, i.e. the difference between the share of an economy's exports and imports that are priced in the dominant currency. Underlying this prediction is a change in an economy's net exports in response to multilateral changes in the US dollar exchange rate that arises because of differences in the extent to which exports and imports are priced in the dominant currency. We then confront this prediction of DCP with the data in a sample of up to 46 advanced and emerging market economies for the time period from 1995 to 2018. Specifically, controlling for other cross-border transmission channels, we document that consistent with the prediction from DCP the output spillovers from US dollar appreciation correlate negatively with recipient economies' export-import US dollar invoicing share differentials. We document that these findings are robust to considering US demand, US monetary policy and exogenous exchange rate shocks as a trigger of US dollar appreciation, as well as to accounting for the role of commodity trade in US dollar invoicing.
Keywords: F42; E52; C50; 330; Dominant-currency pricing; US shocks; spillovers